THE IMPORTANCE OF THE PARADIGM SHIFT IN THE DEVELOPMENT OF DESIGN INDUSTRY AND DESIGN EDUCATION - Irbite, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Literature about design development and the current situation of the essence of trends in this field allow for the defining of design as an independent branch. Analysis of design and education regulations highlights the conflict between reality and gaps that exist in European statistical standards and International Standard Classification of Education. The purpose of this study is to explore complex problems in the field of design and design education which determines the need for Paradigm Shift for further development of these branches, as well as to present proposals for definitions of key terms of design and offer proposals for a new design education classification. This research will show why, and will mark how design needs to be classified individually, and not as a part of visual arts.